INCREASING STUDENT PARTICIPATION THROUGH LEARNING CONCEPT MAP OF EARLY CHILD EDUCATION STUDENTS - Muhammadi Muhammadi; Yusrafiddin Yusrafiddin; Harnon Harnon; Johannes Johannes; Eka Evriza; Kula Ginting (SENSEI RESEARCH CENTER, 2023)
This research is Classroom Action Research (CAR). The research was conducted for 2 cycles with 3 meetings. Methods of data collection using written tests, observation sheets to observe the participation of Early Childhood Education students.The results showed that there was an increase in Student Participation Through Concept Map Learning for Early Childhood Education students. In cycle I it was 52.50% and in cycle II it was 75.83%. So, from cycle I to cycle II, students' reading comprehension ability increased by 23.33%. While the increase in student participation through learning concept maps for Early Childhood Education students in cycle I was 41.67% and in cycle II was 75%. So from cycle I to cycle II it increased 33.33%. Therefore it can be concluded that Concept Map learning can increase student participation in early childhood education.